Determining Covid-19 Disaster Preparedness in Students in Makassar City - Irabuana; Ida Leida Maria; Indrakasih Pratiwi; Adhi Nauval Hafizh Thaha; A. Rinaldy Jaharuddin; Andi Selvi Yusnitasari; Lolah Auliya Muthmainnah; Ummul Qura (Media Kesehatan Masyarakat Indonesia, 2020)
Covid-19 is a disease that has become a pandemic that is very troubling atthis time, including in Indonesia, which until July 16, there were 81,668 witha total of 3,873 deaths. This study aims to determine the determinants thataffect the preparedness of the Covid-19 Pandemic among students inMakassar City. The study was conducted in an observational manner with across sectional study approach. Sampling in this study was conducted usingnon probability sampling technique, namely consecutive sampling. Thisresearch was conducted at 8 universities in Makassar City from April to July2020. The type of data collection used accidental sampling. The results ofdata collection in this study were processed using the Stata 16 applicationwhich was analyzed univariately and bivariately. The results of dataprocessing are presented in the form of tables and are equipped withnarration. The results in this study indicate that there is a relationshipbetween Covid-19 preparedness and knowledge (p=0.049), experience(p=0.013), attitude of respondents (p=0.018). The conclusion of this study isthat knowledge, experience and attitude are determinants of Covid-19preparedness. The author's suggestion is that the government can improveeducation and efforts to implement prevention by the community.